Evaluation the Effect Of Magnetized Water On The Bone Density And Osteoporosis In The Experimental Rats By DXA-Scan - Hassan, Nour Abd Alrazaq; Mubarak, Tahseen Hussain; Gheaeb, Nameer Fadhel (Diyala Journal of Medicine, 2019)
Background: The electromagnetic field used with industrial, and also simultaneous action of those fields on the intensity of bone turnover process in rats was estimated by means of analysis of densitometry. The obtained effect was dependent on frequency and power density of used electromagnetic fields .There was improved in quality of the water when exposed to the electromagnetic field with significant changes in the minerals and organic matter .Therefore it’s penetration into cell wall would be facilitated, which can accelerate ordinary diffusion of water. That is vital for growth and development of different organs .Exposing the water to strong magnetic fields affect in the water`s mineral content , and its effects depended on the "strength of the magnetic field and exposure time". Objective:To study the effect of depreciation the magnetizing water on bone density and osteoporosis for rats. Patients and Methods: In this study It was concluded (14) rat and divided to two groups, A and B "7 rats for each group". Group A feed normal water for 24 days, and group B feed magnetized water for 24 days. The magnetized system that used to magnetized the water consist of 4200 rolled silk around iron tube , and it is connected to the continuous power supply "220 V". and used Digital Gauss meter to measure the magnetic flux equal to 0.9mT. After 24 daily consumption of the magnetized water measure the bone density by DXA scan devise that use to measure the bone mineral density" BMD", bone mineral content "BMC", T-score and Z-score .Comparing the result of " T-score, Z-score, BMD and BMC " between group A and B of the animals after 24 days from consumption the magnetized water. Results: The study shows enhancing in the biological activity in rats that consumption the magnetized, by repairing and turnover the bones in comparing to other group that use normal water. Conclusion: The current study represented the consumptions of magnetized water increase the ability of bone repair and turnover.